E-Business and Telecommunications : 16th International Conference, ICETE 2019, Prague, Czech Republic, July 26–28, 2019, Revised Selected Papers /: 16th International Conference, ICETE 2019, Prague, Czech Republic, July 26–28, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available